1993
DOI: 10.1105/tpc.5.12.1783
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Trafficking of Macromolecules through Plasmodesmata Potentiated by the Red Clover Necrotic Mosaic Virus Movement Protein.

Abstract: Direct evidence is presented for cell-to-cell trafficking of macromolecules via plasmodesmata in higher plants. The fluorescently labeled 35-kD movement protein of red clover necrotic mosaic virus (RCNMV) trafficked rapidly from cell to cell when microinjected into cowpea leaf mesophyll cells. Furthermore, this protein potentiated rapid cell-to-cell trafficking of RCNMV RNA, but not DNA. Electron microscopic studies demonstrated that the 35-kD movement protein does not unfold the RCNMV RNA molecules. Thus, if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 20 publications
2
112
0
Order By: Relevance
“…In addition to TMV and CaMV, the movement proteins of alfalfa mosaic virus (AMV), red clover necrotic mosaic dianthovirus (RCNMV) and several other viruses have been shown to bind single-stranded nucleic acids (Osman et al 1992;Schoumacher et al 1992;Pascal et al 1994). As with TMV P30, these movement proteins bound nucleic acids cooperatively (Citovsky et al 1991;Osman et al 1992;Schoumacher et al 1992); however, the movement protein of RCNMV did not appear to lengthen bound RNA molecules signi¢cantly (Fujiwara et al 1993). Thus, transport through plasmodesmata via movement proteinn ucleic acid intermediates may represent a common mechanism for cell-to-cell spread of many plant viruses.…”
Section: Movement Protein±nucleic Acid Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to TMV and CaMV, the movement proteins of alfalfa mosaic virus (AMV), red clover necrotic mosaic dianthovirus (RCNMV) and several other viruses have been shown to bind single-stranded nucleic acids (Osman et al 1992;Schoumacher et al 1992;Pascal et al 1994). As with TMV P30, these movement proteins bound nucleic acids cooperatively (Citovsky et al 1991;Osman et al 1992;Schoumacher et al 1992); however, the movement protein of RCNMV did not appear to lengthen bound RNA molecules signi¢cantly (Fujiwara et al 1993). Thus, transport through plasmodesmata via movement proteinn ucleic acid intermediates may represent a common mechanism for cell-to-cell spread of many plant viruses.…”
Section: Movement Protein±nucleic Acid Complexesmentioning
confidence: 99%
“…For example, the P30 protein of TMV can bind and, by implication, transport any single-stranded nucleic acid (Citovsky et al 1990(Citovsky et al , 1992a. In contrast, the RCNMV movement protein is capable of tra¤cking ssRNA but not ssDNA or dsDNA (Fujiwara et al 1993), whereas the bean dwarf mosaic begomovirus (BDMV) BL1 movement protein facilitates transport of dsDNA but not ssDNA nor ssRNA molecules (Noueiry et al 1994). However, transport of BDMV dsDNA seems incompatible with biochemical and genetic evidence obtained with another bipartite begomovirus, squash leaf curl virus (SqLCV), for which the transported form is thought to be genomic ssDNA (Pascal et al 1994).…”
Section: Movement Protein±nucleic Acid Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus movement proteins seem to show selectivity for the type of nucleic acid they transport but not the sequence (Mezitt and Lucas 1996). For example the Red Clover Necrotic Mosaic Virus (RCNMV) movement protein of this RNA virus traffics RCNMV RNA as well as nonspecific RNAs, but not single-or double-stranded DNA (Fujiwara et al 1993).…”
Section: Mechanisms For Cell-cell Interactions: Viral Movement Proteimentioning
confidence: 99%
“…Injection of fluorescently labeled movement proteins into leaf cells has shown that the protein itself can rapidly move from cell to cell (Fujiwara et al 1993;Nouiery et al 1994;Waigman et al 1994;Ding et al 1995). Movement proteins have been shown to bind nucleic acids in vitro (Citovsky 1993 and references therein) and facilitate the movement of labeled nucleic acids when co-injected (Fujiwara et al 1993;Nouiery et al 1994;Ding et al 1995). Virus movement proteins seem to show selectivity for the type of nucleic acid they transport but not the sequence (Mezitt and Lucas 1996).…”
Section: Mechanisms For Cell-cell Interactions: Viral Movement Proteimentioning
confidence: 99%